2019
DOI: 10.1177/1528083719832851
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on thermo-mechanical characteristics of treated/untreated Portunus sanguinolentus shell powder-based jute fabrics reinforced epoxy composites

Abstract: The current study deals with the effective usage of Portunus sanguinolentus shell, which is a solid waste in the seafood industry. This Portunus sanguinolentus shell waste was powdered and used as untreated fillers in jute fabrics reinforced epoxy composites. Then Portunus sanguinolentus shell waste powder was treated with chemicals to perform fat removal, deproteination, decarbonization and deacetylation to obtain treated Portunus sanguinolentus shell filler. Three different composites were developed with tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(67 citation statements)
references
References 46 publications
3
64
0
Order By: Relevance
“…ρf, ρn and ρm are density of glass fiber, nanoclay and matrix respectively. ASTM D2734-94 standard is used to evaluate voids fraction of GFENC [19,20]. From the theoretical and actual densities of the GFENC, the void fraction is calculated by equation (2).…”
Section: Composite Specimen Preparationmentioning
confidence: 99%
“…ρf, ρn and ρm are density of glass fiber, nanoclay and matrix respectively. ASTM D2734-94 standard is used to evaluate voids fraction of GFENC [19,20]. From the theoretical and actual densities of the GFENC, the void fraction is calculated by equation (2).…”
Section: Composite Specimen Preparationmentioning
confidence: 99%
“…Valorization of food processing by-products and agricultural waste is acquiring increasing importance due to the high interest in the development of novel sustainable materials as part of the Circular Bioeconomy framework [1,2]. Agro-food wastes, such as flax fibers [3,4], rice husk [5], jute fibers [6,7], almond husk [8,9], walnut husk [10], orange peel [11], coconut fibers [12] or sisal fibers [13], represent examples of recently explored fillers to be incorporated into biopolymer matrices. The resultant green composites can successfully show technological advantages over conventional petroleum derived polymer composites, including cost reduction, lower density, no toxicity, balanced mechanical properties and, more importantly, lower environmental impact [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers reported that the composites with high filler contents (more than 10 wt%) increase the probability of filler agglomeration resulting in poor wetting between fillers and matrix, which will eventually lead to a deterioration of composite strength. [37][38][39][40] In addition, agglomeration behaves as the large single particle at higher filler content, resulting in poor interfacial bonding between the filler and the matrix. Therefore, the less TPS filler content (10 wt %) was used in the present study for the preparation of composite samples.…”
Section: Preparation Of Composite Samplesmentioning
confidence: 99%